N‐Telopeptide of Type I Collagen Long‐Term Dynamics in Breast Cancer Patients With Bone Metastases: Clinical Outcomes and Influence of Extraskeletal Metastases. (17th August 2016) - Ferreira, Arlindo R.; Alho, Irina; Shan, Ning; Matias, Margarida; Faria, Mariana; Casimiro, Sandra; Leitzel, Kim; Ali, Suhail; Lipton, Allan; Costa, Luís
Abstract : Background: Markers of bone metabolism, such as N‐telopeptide of type I collagen (NTX), have been demonstrated to be prognostic in previous trials of breast cancer (BC) patients with bone metastases (BMs). In the present study, we tested the survival effect of the NTX response to zoledronic acid (ZA) at 3 and 12 months in a contemporaneous cohort of BC patients with BMs and evaluated the influence of extraskeletal metastatic disease on NTX variation. Patients and Methods: The present study was a prospective cohort study of consecutive BC patients diagnosed and treated at a single center. Patients presenting with de novo radiological evidence of BMs who started monthly intravenous ZA were included. Urinary NTX was measured at baseline and 1, 3, 6, 9, and 12 months after ZA introduction. Results: Overall, 71 patients were enrolled, 32 with BMs and 39 with BMs plus extraskeletal metastases. The proportion of patients with elevated NTX at baseline and 3 and 12 months was 49.3%, 26.6%, and 34.2%, respectively. The variables associated with survival included age at diagnosis, tumor estrogen receptor status, and NTX at 3 and 12 months. Multivariate analysis showed that, in addition to age at diagnosis, only the 3‐month NTX level was significantly associated with survival. Patients with BMs plus extraskeletal metastases had an erratic NTX variation pattern, unrelated to survival. Conclusion: In the present contemporaneous cohort of BC patients with BMs, the NTX response at 3 months was strongly associated with survival. Furthermore, an early response to ZA was strongly associated with long‐term NTX control. Finally, patients with BMs plus extraskeletal metastases had an erratic NTX variation. Implications for Practice: The present study showed that when accommodating recent therapy innovations and longer patient survival, the N‐telopeptide (NTX) variation at 3 months is strongly associated with survival. In this setting, in addition to a few other clinicopathological features, NTX is a powerful prognostic marker. Moreover, early NTX correction associates with persistently normal NTX. This might identify a subgroup of patients with a good prognosis who are eligible for premature zoledronic acid (ZA) de‐escalation. Finally, patients with bone plus extraskeletal metastases showed an erratic variation of NTX, raising concerns that a single ZA regimen might not fit all patients. Future trials should test its effect according to the presence of extraskeletal involvement. Abstract : Markers of bone metabolism are prognostic in breast cancer (BC) patients with bone metastases (BMs). The survival effect of the N‐telopeptide of type I collagen (NTX) response to zoledronic acid (ZA) and the influence of extraskeletal metastatic disease on NTX variation were evaluated. An early response to ZA was strongly associated with long‐term NTX control. Patients with BMs plus extraskeletal metastases had erratic NTX variations.